Notes on the problems of social research in Latin America - Quijano Obregón, Aníbal (2021)
Aníbal Quijano’s text, which we publish in the Classics of Social Sciences section, aims to open some fundamental epistemological and theoretical questions to understand the profound transformations that were taking place in social research in Latin America from the beginning of the seventies. These reflections have as their starting point the exploration of the crisis of social thought worldwide and its specific characteristics in Latin America. The crisis is presented on two levels: as a “ crisis of paradigms” -where the models of social knowledge that emerged in Europe in the 19th century no longer “allow the production of significant questions about reality”- and as a “crisis of problematics”-which deals with the set of interrelated issues where, in the case of Latin America, in recent years, social research has abandoned issues related to power conflicts and social transformation to focus on merely technocratic needs. Consequently, the author proposes advancing in the task of going towards a new problematics of Latin American social research.